Mobile nucleosomes--a general behavior. - Meersseman, G (1992)
We have previously reported the mobility of positioned nucleosomes on sea urchin 5S rDNA. In this study we demonstrate the temperature dependence and the range of this mobility on 5S rDNA constructs. We find that this dynamic behavior also applies to bulk mononucleosomes and nucleosomes reconstituted onto sequences of the Alu family of ubiquitous repeats. We conclude that short range sliding is potentially a general phenomenon that is dependent on the underlying sequence and its position on the histone octamer. The nucleoprotein gel analysis used also reveals the dramatic effect on gel electrophoretic migration caused by the location of the histone octamer on DNA fragments. The usefulness of this technique for studying nucleosome positioning and its dynamics is demonstrated.